SUPPRESSION EFFORTS BY THE COLONIAL GOVERNMENT AGAINST THE PROTAGONIST IN PRAMOEDYA ANANTA TOER'S HOUSE OF GLASS - Berutu, Achmanudin; Wulan, Sri (Universitas Islam Sumatera Utara, 2024)
This research examines the Dutch colonial government's efforts to suppress the actions of Minke, the protagonist in Pramoedya Ananta Toer's novel House of Glass. Using a descriptive qualitative approach, the study analyzes words, phrases, and sentences in the novel that indicate colonial attempts to hinder Minke’s activities. The methodology involved qualitative data collection focused on identifying events that reflect the colonial government's interventions. The analysis centers on two key aspects: Minke's actions, which include spreading nationalist ideas, organizing movements, leading the SDI (Serikat Dagang Islam), and using speech and writing as tools for resistance. The findings reveal that the colonial government employed various strategies to curb Minke's influence, including surveillance and reporting, legal restrictions and extrajudicial measures, exile of prominent figures, property confiscation, and rumor-spreading. These efforts underscore the colonial regime's reliance on military force and the loyalty of indigenous officials, highlighting its fundamental weaknesses due to a lack of democratic foundations.